Effect of endobronchial aspirin challenge on inflammatory cells in bronchial biopsy samples from aspirin-sensitive asthmatic subjects. - Nasser, S. (1996)
BACKGROUND: The aspirin-induced bronchoconstriction in patients with aspirin-sensitive asthma is caused by cysteinyl leukotriene release. The cellular source of the leukotrienes is unknown. The inflammatory cell infiltrate in bronchial biopsy samples from seven aspirin-sensitive asthmatic (ASA) subjects and eight non-ASA subjects before and after local challenge with lysine aspirin was therefore examined. METHODS: Using flexible bronchoscopy, airway mucosal biopsy samples were taken and lysine aspirin solution was placed directly onto a carina of the contralateral lung. Twenty minutes later a second series of biopsy samples was taken from the site of the local endobronchial lysine aspirin challenge. The biopsy samples were double immunostained with a rabbit polyclonal antibody to the enzyme 5-lipoxygenase and monoclonal antibodies to mast cells (AA1), neutrophils (NP57), macrophages (EBM11), T lymphocytes (anti-CD3), and total (BMK13) and activated eosinophils (EG2). RESULTS: A decrease in both absolute mast cell numbers staining with mast cell tryptase (AA1) and the percentage of mast cells co-immunostaining with 5-lipoxygenase was seen in the ASA patients after lysine aspirin challenge compared with the non-ASA control group. There was also an increase in the numbers of activated eosinophils (EG2) in the ASA subjects compared with the non-ASA group. No changes were observed in the total numbers of macrophages (EBM11), neutrophils (NP57), total eosinophils (BMK13), and T lymphocytes (anti-CD3) after challenge with lysine aspirin. CONCLUSIONS: The decrease in numbers of mast cells staining for tryptase and the increase in activated eosinophils after endobronchial challenge with lysine aspirin may represent degranulation of these cell types, and may be an early event associated with aspirin-sensitive reactions in ASA subjects.